2022
DOI: 10.3390/cells11030515
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes and Macrophages in Spondyloarthritis: Functional Roles and Effects of Current Therapies

Abstract: Spondyloarthritis (SpA) is a family of chronic inflammatory diseases, being the most prevalent ankylosing spondylitis (AS) and psoriatic arthritis (PsA). These diseases share genetic, clinical and immunological features, such as the implication of human leukocyte antigen (HLA) class I molecule 27 (HLA-B27), the inflammation of peripheral, spine and sacroiliac joints and the presence of extra-articular manifestations (psoriasis, anterior uveitis, enthesitis and inflammatory bowel disease). Monocytes and macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 181 publications
(213 reference statements)
0
14
0
Order By: Relevance
“…23 About MTX, it disrupts proliferation of monocytes and macrophages. 26 Also, it downregulates keratinocytes growth and endothelial expression of the cell adhesive molecules ICAM-1, E-selectin. 11 TNFα, IFNγ, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…23 About MTX, it disrupts proliferation of monocytes and macrophages. 26 Also, it downregulates keratinocytes growth and endothelial expression of the cell adhesive molecules ICAM-1, E-selectin. 11 TNFα, IFNγ, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes have also been shown to play a key role in the pathogenesis of SpA. Moreover, monocyte subpopulations were found to be positively correlated with AS disease activity parameters and C-reactive protein levels, and monocytes in AS patients significantly increased phagocytic activity than controls ( 40 ). Recent evidence has shown that NETs are involved in the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that neutrophils may be linked to the role of TNF-α in the inflammatory process of AS via IL-17. In previous studies of patients with AS, monocytes exhibited higher pro-inflammatory properties, and showed more pronounced phagocytic activity as compared to controls [ 36 ]. Although platelets can be involved in the inflammatory process by secreting various cytokines such as IL-6 and transforming growth factor-β, the role of platelets in the pathophysiology of AS has not been well studied.…”
Section: Discussionmentioning
confidence: 99%